First Autochthonous Case of Canine Visceral Leishmaniasis in the Center of Rio Grande do Sul State, Brazil - Da Silva, Aleksandro Schafer; Franca, Raqueli Teresinha; Richini-Pereira, Virginia Bodelao [UNESP]; Langoni, Hélio [UNESP]; Monteiro, Silvia Gonzalez; dos Anjos Lopes, Sonia Terezinha (Universidade Federal do Rio Grande do Sul (UFRGS), 2011)
Background: Leishmaniasis is one of the most important vector-borne diseases of humans. This parasitic disease can be caused by many species of Leishmania. In humans, different species of the parasite are associated with different forms of the disease, cutaneous and visceral. Among domesticated animals, dogs are the most important species in the epidemiology of this disease. Leishmania chagasi, an important zoonosis, is well established as the agent of visceral leishmaniasis in Brazil. The disease is endemic in north, northeast, midwest and southeast, and is transmitted to mammals by hematophagous insects such as the Lutzomyia longipalpis. In 2008, our research group has diagnosed a case of canine leishmaniasis in the municipality of Uruguaiana and subsequently there were several cases in the city and the neighbor municipality of Sao Borja. Most Brazilian states are endemic for leishmaniasis, with the exception of Rio Grande do Sul. In southern Brazil, the reports of humans and dogs infected by Leishmania spp. are the source of endemic area in the country. Therefore, the aim of this study is register the first clinical case of canine visceral leishmaniasis in the municipality of Santa Maria, RS.Case: In october 2010, a veterinary clinic of Santa Maria received a canine, female, Doberman, with two years of age. The animal had severe skin lesions on the head and limbs, pale mucous membranes, and enlarged lymph nodes. According to the owner, the animal showed progressive weight loss and anorexia for more than five days. During the clinical examination the blood was collected for hemogram and cytology of lymph nodes was performed by puncture aspiration with a fine needle. In the erythrogram, it was observed a decrease in the total number of erythrocytes (2.8 x 10(6)/mu L), hematocrit (21%), hemoglobin (6.8 g/dL) and platelets (98 x 10(3)/mu L). In the leucogram, any alteration was observed. The cytology of lymph nodes showed amastigotes forms, suggestive of the Leishmania spp. Based on this finding; we performed the blood collection for PCR, to confirm parasitism and to determine the species of Leishmania. At the molecular test was used PCR-specific for L. chagasi, and the result was positive.Discussion: This is the first autochthonous clinical case in the central region of the RS, non-endemic area for leishmaniasis. In serological studies of visceral leishmaniasis it was diagnosed in five asymptomatic dogs in the municipalities of Santa Maria, Julio de Castilhos and Itaara, however not confirmed by molecular analysis. In the municipalities of Cruz Alta and Uruguaiana cases of L. chagasi have been reported in dogs which previously resided in Leishmania sp. endemic areas. The municipality of Sao Borja had the first record of L. longipalpis in the RS during the leishmaniasis outbreak in 2008-2009. In the central region of the RS vector has not been found, but because in this first autochthonous case dog in Santa Maria believe that the parasite is present and/or doing other insect transmission of leishmaniasis. Clinical signs associated with hematologic and coagulation disorders observed in the canine are commonly described in symptomatic dogs in endemic regions. This case of autochthonous leishmaniasis reinforces the idea of the vector presence in Santa Maria, center of the RS. We believe that canine leishmaniasis is an emerging disease in the southern region of Brazil.
Keywords: Leishmania chagasi; dog; non-endemic area